Digital technologies as a driver of resilience and institutional transformation: The case of Ukrainian agroholdings - Taras Gagalyuk; Maryna Kovalova (International Food and Agribusiness Management Review, 2024)
The present paper explores how implementation of digital technologies (DTs) assists firms in transition economies in addressing weaknesses of the institutional environment surrounding them, in particular via establishment of collective governance systems. Based on case studies of three large-scale agroholdings operating in Ukraine, the paper aims to fill the research gaps with regard to the following: motivation of the firm to initiate DT-enabled collective governance systems; the rules these systems are based on; and the reasons behind the firm's choice of a particular governance mode – closed, shared or open – for these systems. The findings generally support the institutional theory argument that complex technology enables coordination of exchange relationships not only within but also outside firm boundaries. At that, the choice of a governance mode between closed, shared or open institutional infrastructure is likely to depend on the firm's ownership concentration, corporate transparency, availability of resources and social embeddedness.
Keywords: O13; O32; Q16; Q55; Q12; Q15; D02; D23; D25; M11; M14; 330; agroholdings; case studies; digital technologies; institutional infrastructure; Ukraine